The dual functions of the GTPase BipA in ribosome assembly and surface structure biogenesis in Salmonella enterica serovar Typhimurium. - Eunsil Choi; Eunwoo Ryu; Donghwee Kim; Ji-Won Byun; Kahyun Kim; Minho Lee; Jihwan Hwang (PLoS Pathogens)
The bactericidal/permeability-increasing protein (BPI)-inducible protein A (BipA) is a highly conserved protein in Gram-negative bacteria that is structurally similar to translational GTPases such as IF2, EF-Tu, and EF-G. Our previous research showed that deleting bipA in Escherichia coli at 20°C leads to a defect in 50S ribosomal assembly and impaired lipopolysaccharide (LPS) synthesis. This LPS defect activates the Regulator of Capsule Synthesis (Rcs) pathway, resulting in an overproduction of capsular polysaccharides, a reduction in biofilm formation, and decreased flagella-mediated motility. In this study, we aimed to elucidate the role of BipA in the pathogenicity of Salmonella enterica serovar Typhimurium. We constructed bipA deletion mutants in two pathogenic S. Typhimurium strains, SL1344 and 14028, as well as in the attenuated strain LT2. Our ribosome profiling experiments using the mutant S. Typhimurium strains revealed a defect in ribosome assembly at 20°C, with the accumulation of abnormal 50S ribosomal subunits. We further demonstrated that the absence of BipA in S. Typhimurium impaired LPS biosynthesis at 20°C, compromising membrane integrity and presumably activating the Rcs pathway. This activation altered virulence factors, including reduced biofilm formation, particularly in the 14028ΔbipA strain. Furthermore, the SL1344ΔbipA and 14028ΔbipA strains exhibited significantly decreased swimming motility at 20°C compared to 37°C, confirmed by microscopic observation showing fewer flagella at 20°C. Subsequently, both strains exhibited a significant reduction in invasion capability and cytotoxicity toward human intestinal epithelial cells (HCT116). This functional attenuation was corroborated by the decrease in virulence observed in the 14028ΔbipA strain in a mouse model. Our findings suggest that, in S. Typhimurium, BipA functions as a bacterial fitness factor, contributing to ribosome assembly, LPS synthesis, and virulence-related processes, particularly under stress conditions relevant to host environments.